Recurrent Epistaxis due to Bizarre Finding of Supernumerary Nasal Tooth - Firamir Zulkifli; A. B. M. Tofazzal Hossain; Halimuddin Sawali; Shaila Kabir; A. H. M. Delwar; M. Tanveer Hossain Parash; Liew, Constance Sat Lin; Mohd Firdaus Mohd Hayati; Fairrul Masnah @ Kadir; M. Alamgir Chowdhury (Penerbit UMS, 2021)
A supernumerary tooth is an additional tooth that erupted more than the normal dentition. A rarer form of a supernumerary tooth is when it erupted ectopically into the nasal cavity. Since childhood, this case report describes a 32-year-old male patient with recurrent mild nasal bleeding from his left nostril. It was never investigated seriously as the bleeding was mild and infrequent. After he was recently referred to our centre, a thorough Ear, Nose, and Throat examination was done. Direct vision with Hopkins zero-degree rigid endoscope and orthopantomogram computed tomography confirmed the provisional diagnosis of a supernumerary nasal tooth. The patient was offered surgical extraction of the tooth under general anaesthesia. He denied the surgery and decided to have regular follow up. He is maintaining good health without worsening the symptoms.